Use of raw minerals in beads - current trend of decorative art - Trykolenko, Sofia T.; Yelisieiev, Ihor A. (Theory and practice of design, 2022)
One of the most interesting trends in modern jewelry and decorative arts is the use of natural forms in mineral products — unprocessed in general or partially processed. Most of these techniques are used by independent artists and small jewelry workshops, while the mass production of jewelry is based on established trends of equally faceted stones. Artists who make jewelry from beads have inherited this trend from jewelry artists. For traditional beadwork techniques until the beginning of the XXI century, the involvement of raw minerals was not carried out; instead, it was the millennium that became the beginning of a new trend. Luxurious collections are appearing all over the world, which are on the verge of decorative and jewelry art. The development of the Internet has created endless bases for learning and inspiration, thanks to which the methods of working with raw minerals in combination with beads have become well-known. The appeal to minerals of natural forms demonstrates a change in the worldview of artists — from the desire to adapt natural material to their needs to the ability to find an artistic concept of the product that would reveal the beauty of materials without artificial interference with their shape and texture. This article analyzes the principles of using minerals of natural forms in bead products. Such visual concepts embody a powerful layer of content: the ideas of greening, awareness of the power of the elements and, at the same time, the vulnerability of nature, are becoming increasingly common in the civilized world. Barbaric consumption of natural resources is slowly giving way to recovery. At the same time, the art of beadwork is one of the most famous and significant for Ukrainian culture. Historical aspects of the formation of beadwork in the country are considered. Issues such as the educational function of decorative arts are highlighted. The art of making jewelry, as one of the most common and most popular in the world, has absorbed a kind of educational function — a demonstration of the beauty of nature in its wild, untamed state; and the art of making beaded jewelry demonstrates the plasticity and versatility of this material. At the beginning of the XXI century, the direction of making bead frames in combination with large glass or mineral beads, pearls, metal, etc. is gaining ground. This article offers a product of the Ukrainian craftswoman “Baronessainred”, who creates beaded jewelry with a variety of minerals. It is worth noting that the article is a continuation of a series of articles on the trend of using minerals of raw forms in jewelry and decorative arts.